Financial statement analysis workbook : a practitioner's guide - Fridson, Martin S.; Alvarez, Fernando, 1964- (Wiley finance series., 2022)
"This fifth edition of Financial Statement Analysis, like its predecessors, seeks to equip its readers for the practical challenges of contemporary business. Once again, the intention is to acquaint readers who have already acquired basic accounting skills with the complications that arise in applying textbook-derived knowledge to the real world of extending credit and investing in securities. Just as a swiftly changing environment necessitated extensive revisions and additions in the second through fourth editions, new concerns and challenges for users of financial statements have emerged as the third decade of the twenty-first century unfolds"--